2023
DOI: 10.3390/ijms241813892
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Derived Short-Chain Fatty Acids Are Linked to Evolution of Heart Failure Patients

Javier Modrego,
Adriana Ortega-Hernández,
Josebe Goirigolzarri
et al.

Abstract: There is a lack of direct evidence regarding gut microbiota dysbiosis and changes in short-chain fatty acids (SCFAs) in heart failure (HF) patients. We sought to assess any association between gut microbiota composition, SCFA production, clinical parameters, and the inflammatory profile in a cohort of newly diagnosed HF patients. In this longitudinal prospective study, we enrolled eighteen newly diagnosed HF patients. At admission and after 12 months, blood samples were collected for the assessment of proinfla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…A negative correlation was also observed between acetate and NT-proBNP, and a positive correlation was observed with left ventricular ejection fraction (LVEF) and endothelial progenitor cells. Propionate correlated positively with anti-inflammatory activity [39].…”
Section: Short-chain Fatty Acids (Scfas)mentioning
confidence: 94%
See 2 more Smart Citations
“…A negative correlation was also observed between acetate and NT-proBNP, and a positive correlation was observed with left ventricular ejection fraction (LVEF) and endothelial progenitor cells. Propionate correlated positively with anti-inflammatory activity [39].…”
Section: Short-chain Fatty Acids (Scfas)mentioning
confidence: 94%
“…Furthermore, they also demonstrated the positive impact of this phylum of bacteria. They showed that higher levels of Bifidobacterium were associated with lower levels of pro-inflammatory markers and N-terminal pro-Btype natriuretic peptides (NTpro-BNP) and were positively correlated with markers of endothelial function and improved intestinal barrier function [39].…”
Section: Changes In the Composition Of The Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these bacteria have been associated with the severity of the disease as expressed by the New York Heart Association (NYHA) functional classes [16]. With respect to controls, HF patients are also characterized by less abundance of short-chain fatty acid (SCFA)-producing bacteria such as Blautia, Erysipelotrichaceae, Collinsella, Ruminococcaceae, Lachnospiraceae, Faecalibacterium, Eubacterium rectale, and Dorea Longicatena [17][18][19].…”
Section: Gut Microbiota Dysbiosis In Heart Failurementioning
confidence: 99%